Modeling the sustained use of the 13-valent pneumococcal conjugate vaccine compared to switching to the 10-valent vaccine in Mexico - Matthew Wasserman; Maria Gabriela Palacios; Ana Gabriela Grajales; F. Berenice Baez/Revueltas; Michele Wilson; Cheryl McDade; Raymond Farkouh (Taylor & Francis Group, 2019)
Introduction: Pneumococcal diseases caused by Streptococcus pneumoniae represent a significant health and economic burden. Mexico has benefited from the inclusion of the 7-valent (PCV7) and 13-valent pneumococcal conjugate vaccines (PCV13) since their inclusion in the National Immunization Program (NIP) in 2006 and 2010, respectively. The objective of this study is to estimate the impact of the existing program and predict future implications of a change in the current program. Methods: A previously published model was updated to estimate the historic impact of the PCV programs relative to pre-PCV implementation. Future disease trends were forecasted based on historical serotype behaviors for each PCV13 serotype and non-vaccine serotypes across different age groups. Costs and outcomes were estimated over a 10-year period based on continued use of PCV13 compared to a switch to PCV10. Results: The PCV7 and subsequent PCV13 NIP were estimated to prevent over 1.5 million cases of pneumococcal disease and 1,854 deaths, corresponding to a net savings of $34.50 Billion MXN. Continued use of PCV13 was estimated to save over 300 thousand cases of pneumococcal disease and 373 deaths compared to switching to PCV10 over a 10-year period. Despite a higher vaccine cost, maintaining PCV13 was cost-saving compared to PCV10, saving $6.71 billion MXN over 10 years. Conclusion: The PCV program in Mexico has provided a significant return on investment. Sustained PCV13 use was estimated to provide the greatest healthcare and economic impact in Mexico. Changes to the pneumococcal vaccination program could result in serotype replacement and reduction in herd effects.